THE EFFECT OF OMEPRAZOL ON THE LIVER REGENERATION AND THE GASTRIC ACIDITY OF THE PARTIALLY HEPATECTOMIZED RATS - Musa AKOĞLU; Vedat KIRIMLIOĞLU; Uğur YILMAZ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-